Effect of ion concentration of ionomer in electron injection layer of polymer light-emitting devices - Olivati, C. A.; Carvalho, A. J. F.; Balogh, D. T.; von Seggern, H.; Faria, R. M. (Elsevier B.V., 2006)
Polymer light-emitting devices (PLEDs) with poly(2-methoxy-5-hexyloxy)-p-phenylenevinylene (OC1OC6-PPV) as the emissive layer were studied with an electron injection layer of ionomers consisting of copolymers of styrene and methylmethacrylate (PS/PMMA) with 3, 6 and 8 mol% degree of sulfonation. The ionomers were able to form very thin films over the emissive layer, with less than 30 nm. Additionally, the presence of ion pairs of ionomer suppresses the tendency toward dewetting of the thin film of ionomer (similar to 10 nm) which can cause malfunction of the device. The effect of the ionomers was investigated as a function of the ion content. The devices performance, characterized by their current density and luminance intensity versus voltage, showed a remarkable increase with the ionomer layer up to 6 mol% of ionic groups, decreasing after that for the 8 mol% ionomer device. The study of the impedance spectroscopy in the frequency range from 0.1 to 10(6) Hz showed that the injection phenomena dominate over the transport in the electroluminescent polymer bulk. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: conductivity; electroluminescence; polymer and organics